Kandungan asam p-Hidroksibenzoat dan p-Kumarat akar padi varietas inpara dan pengaruhnya terhadap pertumbuhan Echinochloa crus-galli - Sujinah Sujinah; Swisci Margaret; Indrastuti Apri Rumanti; Nurwulan Agustiani (Jurnal AGRO, 2023)
Compounds of p-hidroksibenzoic and p-coumaric acids are allelochemicals produced by plants and can be phytotoxic to other plants. Allelochemicals can be used as bioherbicides in weed control. The objective of this research was to determine the content of p-hydroxybenzoic and p-coumaric in rice roots, and their effect on the growth of barnyard grass (Echinochloa crus-galli). Analysis of the content of p-hydroxybenzoic and p-coumaric compunds was carried out using HPLC. The experiment on E. crus-galli growth consisted of two phases using a completely randomized design with three replications. The first phase was testing of compounds with various concentrations (100, 300, 500, 700 ppm), and the second phase was testing of rice root extracts 0.5 g ml-1 on several Inpara varieties. The result showed that the highest content of p-hydroxybenzoic and p-coumaric acids was found in Inpara 9, and the lowest was in Inpara 6. The greatest inhibition of E. crus-galli growth (shoot and root length, dry weight) was observed at 700 ppm concentration. Rice root extracts inhibit the growth of E. crus-galli with varying degrees. Inpara 3, 4, 7, 8, and 10 had the ability to suppress E. crus-galli growth higher than the average of 10 Inpara varieties used.ABSTRAK Senyawa asam p-hidroksibenzoat dan p-kumarat merupakan alelokimia yang diproduksi oleh tanaman dan dapat bersifat fitotoksik terhadap tanaman lain. Alelokimia dapat dimanfaatkan sebagai bioherbisida dalam pengendalian gulma. Penelitian ini bertujuan untuk mengetahui kandungan p-hidroksibenzoat dan p-kumarat pada akar padi, serta pengaruhnya terhadap pertumbuhan jajagoan (Echinochloa crus-galli). Analisis kandungan senyawa p-hidroksibenzoat dan p-kumarat dilakukan dengan menggunakan HPLC. Pengujian terhadap pertumbuhan E. crus-galli terdiri dari dua tahap dengan menggunakan Rancangan Acak Lengkap tiga ulangan. Tahap pertama adalah pengujian senyawa dengan berbagai konsentrasi (100, 300, 500, 700 ppm) dan tahap kedua adalah pengujian ekstrak akar padi dengan konsentrasi 0,5 g ml-1 pada beberapa varietas Inpara. Hasil penelitian menunjukkan bahwa kandungan asam p-hidroksibenzoat dan p-kumarat tertinggi terdapat pada Inpara 9, dan yang terkecil pada Inpara 6. Penghambatan pertumbuhan E. crus-galli (panjang tajuk, akar, dan berat kering) terbesar pada konsentrasi 700 ppm. Ekstrak akar padi mampu menghambat pertumbuhan E. crus-galli dengan tingkat penghambatan yang bervariasi. Inpara 3, 4, 7, 8, dan 10 memiliki kemampuan menekan pertumbuhan E. crus-galli lebih tinggi dari rata-rata 10 varietas yang digunakan.